Pengembangan Media Pembelajaran Berbasis Game Edukasi Pada MatPel IPA Tematik Kebersihan Lingkungan - Reni Widyastuti; Listia Sari Puspita (Paradigma, 2020)
Game is one of the interactive multimedia products which is developing rapidly in the world, including Indonesia. Educational games can be used as an alternative interactive learning media that has the goal of supporting the learning process with the concept of "playing while learning". The educational game aims to stimulate students to understand the material provided by the teacher and help teachers provide alternative teaching methods that are fun for students. Environmental cleanliness is a learning theme for grade 1 elementary school presented on Natural Sciences (IPA) subjects. First grade elementary school students are early students who want fun learning so the purpose of this research is to create an educational mobile game application that can be used for learning media for elementary school class I science that can motivate students to learn, understand and apply environmental cleanliness starting from home, school and can distinguish waste that can be recycled or not. In the construction of this game using the version 2 construct application with system development with the waterfall system development method